2021
DOI: 10.3389/fevo.2021.738199
|View full text |Cite
|
Sign up to set email alerts
|

Dendrochronology in European Russia in the Early 21st Century: State of the Art

Abstract: In this review, we have focused on the following key points: (1) living trees in European Russia and their climatic sensitivity. Species suitable for tree-ring analyses, their age limits, spatial distribution of temperature- and drought-sensitive trees, and the available tree-ring chronologies. (2) Extension of the living-tree chronologies using archeological and architectural samples. Dendrochronological dating of archeological and cultural monuments. (3) Tree-ring-based climatic reconstructions in European R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Sophisticated knowledge of mechanical properties and other characteristics of various tree species by historical craftsmen can be expected (Blau, 1917). The regional preference of a species is strongly affected by its natural distribution (Kolář et al, 2021;Shindo and Giraud, 2021;Sochová et al, 2021;Solomina and Matskovsky, 2021). For example, in the lowlands of western Europe oak was regularly used for all components of vernacular buildings due to the rare occurrence of conifers (Haneca et al, 2009;San-Miguel-Ayanz et al, 2016).…”
Section: Wood From Historical Buildingsmentioning
confidence: 99%
“…Sophisticated knowledge of mechanical properties and other characteristics of various tree species by historical craftsmen can be expected (Blau, 1917). The regional preference of a species is strongly affected by its natural distribution (Kolář et al, 2021;Shindo and Giraud, 2021;Sochová et al, 2021;Solomina and Matskovsky, 2021). For example, in the lowlands of western Europe oak was regularly used for all components of vernacular buildings due to the rare occurrence of conifers (Haneca et al, 2009;San-Miguel-Ayanz et al, 2016).…”
Section: Wood From Historical Buildingsmentioning
confidence: 99%
“…These last two types of chronologies are not connected to any living-tree chronology from nearby locations. A more detailed description of the current state of dendrochronological data and research in the region may be found in the recent review 16 .…”
Section: Background and Summarymentioning
confidence: 99%